2013
DOI: 10.1021/ac4025279
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Mass Spectrometry Sampling Probe for Chemical Analysis in Surgical and Endoscopic Procedures

Abstract: A sampling probe based on ambient desorption ionization was designed for in-vivo chemical analysis by mass spectrometry in surgical and endoscopic procedures. Sampling ionization of analytes directly from tissue was achieved by sealing the sampling tip against the tissue surface without allowing leakage of the auxiliary gas used for desorption ionization. The desorbed charged species were transferred over a long distance (up to 4 m) through a flexible tube of internal diameter as small as 1/16 inch to the inle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 62 publications
(107 reference statements)
1
31
0
Order By: Relevance
“…Intraoperative diagnosis and surgical margin evaluation continue to be research focuses of clinical ambient ionization MS, with efforts used to develop devices for in vivo diagnosis (18). For example, a sampling probe using a DESI-MSI source to produce a continuous high-pressure spray of microdroplets has been proposed for tissue analysis (38), but it has not been demonstrated for cancer diagnosis or in vivo use. Ultraviolet and infrared laser approaches have been reported for tissue analysis through ablation processes (23, 24).…”
Section: Discussionmentioning
confidence: 99%
“…Intraoperative diagnosis and surgical margin evaluation continue to be research focuses of clinical ambient ionization MS, with efforts used to develop devices for in vivo diagnosis (18). For example, a sampling probe using a DESI-MSI source to produce a continuous high-pressure spray of microdroplets has been proposed for tissue analysis (38), but it has not been demonstrated for cancer diagnosis or in vivo use. Ultraviolet and infrared laser approaches have been reported for tissue analysis through ablation processes (23, 24).…”
Section: Discussionmentioning
confidence: 99%
“…25 Some recent studies have shown the potential of using real-time MS analysis to provide rich molecular information on tissue to assist in surgical decision making. 5,35,36 The use of a miniature MS system, instead of a lab-scale mass spectrometer, would certainly make the implementation of real-time MS analysis much more convenient in surgical room.…”
Section: Resultsmentioning
confidence: 99%
“…Auxiliary pumping was used to pull the gas for ion transfer, which altered the gas dynamics of the sampling area and minimized the destruction to the tissue surface. 25 …”
Section: Introductionmentioning
confidence: 99%
“…One used a remote sampling desorption ESI of over 1 m. 31) Unlike the normal operation, the sampling tip of the remote DESI had to be pressed against the tissue sample to seal o the gap so as to direct the carrier gas and ions to the MS inlet. To meet the clinical requirement, the high voltage supply to the ESI source had to be removed, and the solvent needed to be replaced with pure water.…”
Section: Incorporation Of Ambient Ms To Endoscopementioning
confidence: 99%